Perineural Ultrasound-Guided Catheter Bacterial Colonization: A Prospective Evaluation in 747 Cases. Issue 6 (1st October 2011) - Aveline, Christophe; Le Hetet, Hubert; Le Roux, Alain; Vautier, Pierre; Gautier, Jean François; Cognet, Fabrice; Auger, Philippe; Bonnet, Francis
Abstract : Background and Objectives: Ultrasound guidance is increasingly used for catheter insertion and could make it more complicated to guarantee aseptic insertion of catheters. The current study evaluated the incidence of colonization of ultrasound-guided perineural catheter (US-PNC) placed for postoperative analgesia. Methods: We evaluated prospectively for 14 months 760 ultrasound-guided catheters in a single center placed under sterile conditions. Quantitative culture of all the catheters was performed after withdrawal. Colonization was defined as ≥10 3 colony-forming units/mL. Infection was defined as the isolation of the same microorganism from the colonized catheter and from blood culture and/or culture of an abscess. Univariate and multivariate logistic regression analyses were performed to determine the independent risk factors of US-PNC colonization. Results: Incidences of colonization and infections were 10.4% (95% confidence interval [95% CI], 8.2%-14.4%) and 0.13% (95% CI, 0%-3.8%), respectively, in a total of 747 catheters. Coagulase-negative staphylococci colonization was documented in 69% of the colonized catheters. Local inflammation was more frequently noted when catheters were colonized (26.9% [95% CI, 15.2%-38.7%] versus 8.1% [95% CI, 4.2%-11.9%], P = 0.005). Independent factors for ultrasound-guided catheter colonization were duration of catheter placement more than 48 hours (odds ratio [OR], 4.9; 95% CI, 1.1-12.7; P = 0.003), diabetes (OR, 2.3; 95% CI, 1.4-9.6; P = 0.004), and antibiotic administration during the month preceding surgery (OR, 1.8; 95% CI, 1.5-7.8; P = 0.01). Conclusions: Although infection rate is low, there is a risk of ultrasound-guided catheter colonization that deserves careful monitoring of the insertion site in the postoperative period.